2017
DOI: 10.1111/jcpp.12712
|View full text |Cite
|
Sign up to set email alerts
|

Structural and functional connectivity in children and adolescents with and without attention deficit/hyperactivity disorder

Abstract: Background: Attention deficit/hyperactivity disorder (ADHD) has frequently been associated with changes in resting-state functional connectivity, and decreased white matter (WM) integrity. In the current study, we investigated functional connectivity within Default Mode and frontal control resting-state networks (RSNs) in children with and without ADHD. We hypothesized the RSNs of interest would show a pattern of impaired functional integration and segregation and corresponding changes in WM structure. Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
61
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(70 citation statements)
references
References 57 publications
(74 reference statements)
7
61
2
Order By: Relevance
“…In addition, our results showed a similarly widespread pattern in several functional sub-networks, mainly the default mode, but also attention, salience, fronto-parietal and auditory nodes, among others ( Figure 5). Although the latter results did not survive FDR correction, they provide the basis to infer the potential functional systems being affected in ADHD, being consistent with the current theories involving such networks (Castellanos and Aoki, 2016), particularly with the DMN interference hypothesis, which is based on the findings of altered interactions between the DMN and networks involved in top-down executive control (Fox et al, 2005(Fox et al, , 2007Kelly et al, 2008;Castellanos and Aoki, 2016;Elton et al, 2014;Hoekzema et al, 2014;Bos et al, 2017;Qian et al, 2019).…”
Section: Discussionsupporting
confidence: 74%
“…In addition, our results showed a similarly widespread pattern in several functional sub-networks, mainly the default mode, but also attention, salience, fronto-parietal and auditory nodes, among others ( Figure 5). Although the latter results did not survive FDR correction, they provide the basis to infer the potential functional systems being affected in ADHD, being consistent with the current theories involving such networks (Castellanos and Aoki, 2016), particularly with the DMN interference hypothesis, which is based on the findings of altered interactions between the DMN and networks involved in top-down executive control (Fox et al, 2005(Fox et al, , 2007Kelly et al, 2008;Castellanos and Aoki, 2016;Elton et al, 2014;Hoekzema et al, 2014;Bos et al, 2017;Qian et al, 2019).…”
Section: Discussionsupporting
confidence: 74%
“…Extant imaging studies have reported brain structural and functional differences between patients with ADHD and HCs, both in childhood and adulthood. Many functional magnetic resonance imaging (fMRI) findings heavily support that ADHD involves a distributed pattern of brain alterations 3,4 . According to Rubia et al, functional abnormalities in fronto-cortical and fronto-subcortical networks are core deficits in both children and adults with ADHD 5 .…”
Section: Introductionmentioning
confidence: 99%
“…Increased FC was reported in the right inferior frontal gyrus and bilateral prefrontal cortex within the default mode and frontal control networks in participants with ADHD . It was reported that 8.3% smaller total cerebellar volume was observed in boys with ADHD, furthermore a significant decrease was noted only in the frontal lobes in terms of lobar volume .…”
Section: Discussionmentioning
confidence: 93%
“…Increased FC was reported in the right inferior frontal gyrus and bilateral prefrontal cortex within the default mode and frontal control networks in participants with ADHD. 41 It was reported that 8.3% smaller total cerebellar volume was observed in boys with ADHD, furthermore a significant decrease was noted only in the frontal lobes in terms of lobar volume. 42 In our study, compared with the control group according to IC26 which was identified frontal network, FC in ADHD have not changed in the left areas and decreased in the right areas in the frontal network when considering volume in total.…”
Section: Discussionmentioning
confidence: 95%